2015
DOI: 10.1016/j.copsyc.2015.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, obesity and adolescent risk behaviors: current research and future directions

Abstract: Adolescents are particularly vulnerable to risk behaviors as, in this life stage, they are experiencing intense physical, psychological and social changes. Adolescents who are overweight/obese, but particularly those who perceive themselves as such, are more likely to engage in risk behaviors than those who are or perceive themselves of normal-weight. Weight stigma and discrimination may contribute to this association as they reinforce poor body image and create intense stress. Stress is associated with poor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…From that time on, research has increasingly focused on social stigma and victimization in its various manifestations. A large-scale longitudinal US nation wide study showing that when compared to average-weight students, overweight adolescents (aged [13][14][15][16][17][18] were more likely to be socially isolated and less likely to be nominated as friends by their peers [12]. A more recent review underscores previous findings and shows that overweight children are more likely to be victimized by their peers, frequently in a verbal form, and are at higher risk of developing further psychosocial problems [13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…From that time on, research has increasingly focused on social stigma and victimization in its various manifestations. A large-scale longitudinal US nation wide study showing that when compared to average-weight students, overweight adolescents (aged [13][14][15][16][17][18] were more likely to be socially isolated and less likely to be nominated as friends by their peers [12]. A more recent review underscores previous findings and shows that overweight children are more likely to be victimized by their peers, frequently in a verbal form, and are at higher risk of developing further psychosocial problems [13].…”
Section: Introductionmentioning
confidence: 97%
“…obese children victims of bullying. Moreover, the negative emotional consequences associated to weight stigma entail not only the risk of depression and low self-esteem [15], but also reinforce poor body image, and eventually lead to greater engagement in risk behaviours [16]. A study carried out among public school children aged 7-12 informed that almost onequarter of girls and 12% of boys who had been victims of weight-based teasing reported attempting suicide, which is significantly higher compared with 8.5% of girls and 4% of boys who were not teased [17].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, adolescents express more appearance dissatisfaction (Cohn et al ., ), experience more conflict between their ideal and current bodies (Friedman & Brownell, ), more often diet and lift weights to improve social desirability and attractiveness (Byely, Archibald, Graber, & Brooks‐Gunn, ; Cusumano & Thompson, ), and are more concerned with physical attractiveness (Jones, Vigfusdottir, & Lee, ; Rosenblum & Lewis, ) than children. The transition from childhood to adolescence is thus marked by increased attention to attractiveness (e.g., appearance‐related social comparisons; Farhat, ; Jones et al ., ), internalization of the thin and muscular ideals depicted in the media (Parkinson, Tovee, & Cohen‐Tovee, ), and relational aggression towards peers with obesity (Fox & Farrow, ; Janssen, Craig, & Boyce, ). This heightened focus on appearance may make thinness and muscularity criteria for admission to high‐status social groups, may make obesity a particularly salient dimension for social categorization, and is consistent with evidence that adolescents with obesity are at risk for social and emotional difficulties (Roberts & Duong, ; Schaefer & Simpkins, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of different researches show that students suffering from ADHD have more high-risk behaviors, and experience alcohol abuse and eating disorders more than normal students [13][14][15]. In a research it is observed that there is negative relationship between high-risk and self-injurious behaviors of teenagers and their psychic and physical health [16].…”
Section: Introductionmentioning
confidence: 99%